PERADABAN ISLAM DI NUSANTARA MASA MODERN DAN PERKEMBANGAN PENDIDIKANNYA - Farhatul Maula Dzunnuroini; Lutfiah Kurdiana Putri; Ahmad Affandy; M. Anang sholikhudin (CV. BAROKAH PUBLISHER, 2026)
This research aims to explore the historical journey and transformation of Islamic education in Indonesia, from its early arrival to the modernization process in the contemporary era. Islamic education in the archipelago plays a strategic role in shaping social character through spiritual and intellectual values. Using a descriptive-explorative qualitative method and library research, this study analyzes various data from books, journals, and historical documents. The results show that Islamic education developed gradually, starting from simple methods in mosques and prayer rooms (surau) to the birth of institutionalized entities such as pesantren and madrasah. The modernization of Islamic education became massive in the early 20th century as a response to the Dutch colonial education system and reform movements from the Middle East. This process was carried out by integrating traditional classical systems with modern formal schooling. In conclusion, Islamic education in Indonesia has successfully adapted to the dynamics of time through an inclusive cultural approach, enabling it to produce generations with both spiritual depth and broad intellectual insight.